Jayapura Regency Government's Strategy in Flood Disaster Management in Sentani District - Rohmadin, Sulthon; Eryati, Nuzulul Aulia; Batubara, Yusi Eva (Jurnal Indonesia Sosial Sains, 2024)
Sentani District in Jayapura Regency often faces floods that have a significant impact on people's lives, infrastructure, and the environment. High rainfall intensity, geographical conditions, and suboptimal spatial management are the main factors causing flooding in this region. The floods that occurred not only damaged people's homes, but also disrupted economic and social activities, and caused huge losses to the community and local government. The aim of this research is to analyze and formulate appropriate strategies to be used by the Jayapura Regency Government in managing flood disasters, especially in the Sentani District, in order to find out appropriate steps that can be implemented in resolving the problems of flood disasters that frequently occur. The research method used is descriptive qualitative through an inductive approach. Apart from that, the author's data sources are people, places, and documents, with data collection techniques using interviews, observation, and documentation. The theory used by researchers is strategic theory using SOAR analysis. This research produced 5 (five) strategies for flood management. By implementing the right strategy and good collaboration between stakeholders, it is hoped that it can reduce the risk and impact of flood disasters and increase community resilience in facing these disasters.